2020
DOI: 10.3390/cells9051129
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ultrasound-Mediated Intracellular Ca2+ Oscillations in HIT-T15 Pancreatic β-Cell Line

Abstract: In glucose-stimulated insulin secretion (GSIS) of pancreatic β-cells, the rise of free cytosolic Ca2+ concentration through voltage-gated calcium channels (VGCCs) triggers the exocytosis of insulin-containing granules. Recently, mechanically induced insulin secretion pathways were also reported, which utilize free cytosolic Ca2+ ions as a direct regulator of exocytosis. In this study, we aimed to investigate intracellular Ca2+ responses on the HIT-T15 pancreatic β-cell line upon low-intensity pulsed ultrasound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…As can be seen in Figure 1 , low-intensity pulsed ultrasound (LIPUS) was manufactured in a 24-well plate according to a previously reported protocol [ 33 , 34 ]. The distance between the transducer and the plate was 16 mm and was filled with distilled water in order to deliver good ultrasound ( Figure 1 A,B).…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen in Figure 1 , low-intensity pulsed ultrasound (LIPUS) was manufactured in a 24-well plate according to a previously reported protocol [ 33 , 34 ]. The distance between the transducer and the plate was 16 mm and was filled with distilled water in order to deliver good ultrasound ( Figure 1 A,B).…”
Section: Methodsmentioning
confidence: 99%
“…After receiving biomechanical stimulation, cells can alter intracellular calcium concentration through a variety of membrane-dependent pathways: (1) Activation of L-type or T-Type voltage-gated ion channels by increasing channel activity and protein expression levels [ 43 , 44 ]. (2) Activation of the purinergic receptor family on the cell membrane is activated, where mechanical signaling receptors on the cell membrane are activated, causing the ATP or ADP increases, and the purinergic signal can upregulate the expression of P2Y1 receptors [ 45 , 46 ]. (3) Activation of the TRP family of cation channels, TRPV4, which exhibits moderate permeability to calcium ion, is activated to alter the permeability of the cell membrane and promote the inward flow of calcium ion [ 47 , 48 ].…”
Section: Mechanism Of Electromagnetic Fields-induced Calcium Ion Osci...mentioning
confidence: 99%
“… Parvizi et al (2002) reported that both transient and sustained intracellular calcium elevations can be observed in primary rat chondrocytes upon LIPUS exposure. Since then, ultrasound-induced calcium responses were monitored in different types of cells ( Tyler et al, 2008 ; Hwang et al, 2014 ; Weitz et al, 2017 ; Yoon et al, 2020 ), and found to be directly linked with the activation of various mechanosensitive proteins ( Ibsen et al, 2015 ; Yoon et al, 2017 ; Qiu et al, 2019 ; Yoo et al, 2022 ). Based on the observation that intracellular calcium dynamics can be regulated by ultrasound, a modular method has been developed to engineer immune cells with synthetic genetic circuits that can sense and transduce ultrasound stimulation.…”
Section: Apply Mechanobiology To Engineer Immune Cellsmentioning
confidence: 99%